PENGARUH RETURN ON ASSET, EARNING PER SHARE, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM MELALUI KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2018-2022 - Fathimah, Siti; Novi Susyani (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The aim of this research is to determine the impact of return on assets, earnings per share, and debt to equity ratio on stock prices through dividend policy as an intervening variable. The research is quantitative research that uses secondary data in data collection. The research sample used a purposive sampling technique, namely 13 properties and real estate companies in 5 years. This research data analysis uses path analysis. This research found that return on assets has a positive impact on dividend payout ratio, while debt-to-equity ratio and earnings per share have no impact on dividend payout ratio.The test results also show debt to equity ratio have a negative impact on stock prices, while return on asset, earnings per share and dividend payout ratio have a positive impact on stock prices. This research also shows that dividend payout ratio does not influence the relationship between return on asset, debt to equity ratio, earnings per share and stock prices. Keyword : return on asset, earning per share, debt to equity ratio, stock price, dividend payout ratio